Some Terminological Inconsistencies in Norwegian Syntax - Skommer, Grzegorz (Studia Germanica Posnaniensia, 2018)
The subject of the author's considerations is the lack of agreement in the classification of subordinate sentences in Polish and Norwegian grammar. The author suggests that there is a need to base this classification on the relevant parts of a sentence, and not on parts of speech. In this way one can avoid confusion in the acquisition of subordinate clause of the Norwegian language by Poles learning Norwegian.